2013
DOI: 10.1104/pp.113.225730
|View full text |Cite
|
Sign up to set email alerts
|

Plantation Forestry under Global Warming: Hybrid Poplars with Improved Thermotolerance Provide New Insights on the in Vivo Function of Small Heat Shock Protein Chaperones    

Abstract: Climate-driven heat stress is a key factor affecting forest plantation yields. While its effects are expected to worsen during this century, breeding more tolerant genotypes has proven elusive. We report here a substantial and durable increase in the thermotolerance of hybrid poplar (Populus tremula 3 Populus alba) through overexpression of a major small heat shock protein (sHSP) with convenient features. Experimental evidence was obtained linking protective effects in the transgenic events with the unique cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 57 publications
(98 reference statements)
2
21
0
5
Order By: Relevance
“…They bind and stabilize their client proteins that have become denatured under stress conditions. Most of them are highly up‐regulated in response to heat and have a clear role in thermotolerance (Atkinson and Urwin, ; Merino et al ., ; Sun et al ., ; Waters, ). Three AsHSP genes examined in this study, AsHSP17 (Sun et al ., ), AsHSP26.7 and AsHSP26.8 (Wang and Luthe, ), were all significantly induced, but differentially regulated in WT and the TG plants (Figure ), suggesting Fld implication in triggering one of the important stress response mechanisms, contributing to an enhanced plant tolerance to heat.…”
Section: Discussionmentioning
confidence: 99%
“…They bind and stabilize their client proteins that have become denatured under stress conditions. Most of them are highly up‐regulated in response to heat and have a clear role in thermotolerance (Atkinson and Urwin, ; Merino et al ., ; Sun et al ., ; Waters, ). Three AsHSP genes examined in this study, AsHSP17 (Sun et al ., ), AsHSP26.7 and AsHSP26.8 (Wang and Luthe, ), were all significantly induced, but differentially regulated in WT and the TG plants (Figure ), suggesting Fld implication in triggering one of the important stress response mechanisms, contributing to an enhanced plant tolerance to heat.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression of some sHSPs has been detected in all plant tissues under different conditions (Almoguera et al 1993;Coca et al 1996;Sun et al 2001;Verdaguer et al 2003;Swindell 2006;Swindell et al 2007;Qin et al 2008;Siddique et al 2008;Waters et al 2008;Sarkar et al 2009;Weston et al 2011;Haq et al 2013;Merino et al 2014;Park et al 2015). In rice, the Oshsp26 gene was induced by heat stress: the transcript level was the highest when rice leaves were treated at 42°C for 2 h. It was also found that Oshsp26 gene was expressed following oxidative stress even in the absence of heat stress (Lee et al 2000).…”
Section: Introductionmentioning
confidence: 91%
“…In tobacco, constitutive expression of the tomato mitochondrial small heat shock protein enhanced thermotolerance in transgenic plants (Sanmiya et al 2004). A substantial and durable increase in the thermotolerance through overexpression of a major small heat shock protein (sHSP) was also achieved in hybrid poplar (Populus tremula × Populus alba) (Merino et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Heat tolerance is associated with induced expression of heat-shock proteins in plants (Queitsch et al, 2000;Sun et al, 2002;Zhong et al, 2013). Overexpression of HSP leads to enhanced heat tolerance has also been observed in various plant species (Kim et al, 2012;Merino and G omez, 2014;Mu et al, 2013;Murakami et al, 2004;Sato and Yokoya, 2008;Sun et al, 2012). In creeping bentgrass, chloroplast-localized small heat-shock proteins (CP-sHSPs) play an important role in heat tolerance (Wang and Luthe, 2003).…”
Section: Mir393 Positively Regulates Plant Heat Stress Response In Crmentioning
confidence: 99%